Considering Silences in Narrative Inquiry: An Intergenerational Story of a Sami Family - Blix, Bodil Hansen; Caine, Vera; Clandinin, D. Jean; Berendonk, Charlotte (Journal of Contemporary Ethnography, 2021)
Through coming alongside a Sami family, we open spaces to contemplate multiple forms of silence. We argue that rather than the antithesis to narrative, silence is an integral part of narrative inquiry. As narrative inquirers we need to be wakeful to what is told and also untold, often simultaneously. We believe that narrative inquiry is not necessarily about breaking silences, but it is also about honoring silences, as well as the practice of silence. By calling forward one author’s intergenerational experiences, we explore different aspects of silence such as silence as text, silence as context for living and telling, and silences following silencing. We explore how we live with, and within, silences, and how our told and untold stories are shaped by silences and, in turn, also shape silences.